E-Selectin/AAV2/2 Gene Therapy Alters Angiogenesis and Inflammatory Gene Profiles in Mouse Gangrene Model - Ribieras, Antoine J.; Ortiz, Yulexi Y.; Li, Yan; Huerta, Carlos T.; Le, Nga; Shao, Hongwei; Vazquez-Padron, Roberto I.; Liu, Zhao-Jun; Velazquez, Omaida C. (Frontiers in Cardiovascular Medicine, 2022)
For patients with chronic limb-threatening ischemia and limited revascularization options, alternate means for therapeutic angiogenesis and limb salvage are needed. E-selectin is a cell adhesion molecule that is critical for inflammation and neovascularization in areas of wound healing and ischemia. Here, we tested the efficacy of modifying ischemic limb tissue by intramuscular administration of E-selectin/AAV2/2 (adeno-associated virus serotype 2/2) to modulate angiogenic and inflammatory responses in a murine hindlimb gangrene model. Limb appearance, reperfusion, and functional recovery were assessed for 3 weeks after induction of ischemia. Mice receiving E-selectin/AAV2/2 gene therapy had reduced gangrene severity, increased limb and footpad perfusion, enhanced recruitment of endothelial progenitor cells, and improved performance on treadmill testing compared to control group. Histologically, E-selectin/AAV2/2 gene therapy was associated with increased vascularity and preserved myofiber integrity. E-selectin/AAV2/2 gene therapy also upregulated a panel of pro-angiogenic genes yet downregulated another group of genes associated with the inflammatory response. This novel gene therapy did not induce adverse effects on coagulability, or hematologic, hepatic, and renal function. Our findings highlight the potential of E-selectin/AAV2/2 gene therapy for improving limb perfusion and function in patients with chronic limb-threatening ischemia.